Quality Teaching, Learning Language and Technology in Didactic Practice on the Time of Pandemic - Larbi, Sarah Ben (Pattimura University, 2021)
It is in the dynamics of a world out of step, sometimes disoriented, strongly impacted by the Covid19 Coronavirus pandemic in particular, the 21 st century presents itself as a new world exposing a new geo-political map: the world is moving, changing vertiginously at an incredible speed ! Then, the prerogatives of education presupposed in traditional pedagogy have been called into question by new didactic prerogatives. And it is indeed in this pandemic context that researchers, linguists, and educational specialists are reflecting on the dizzying development of digital technology by innovating new approaches that are becoming the backbone of the educational challenge because learning is variable over time. In this international conference, as an invited speaker, we ask the main following question : to what extent does our study fit in with current pedagogical and technological innovation ? So we define the concept of quality in the context of educational sciences and its relationship between language learning (French /English) and technology. Computer sciences (the tool of ICT, distance learning) are an asset to Faerber (2002) Model of “pedagogical tetrahedron’. This is why quality assessment procedures for language learning (acquisition, cognitive training and distance learning) are essential. However, Our study is structured in three ways : firstly, it defines three concepts : the quality of teaching, language learning (French/English) and distance learning, secondly, the author examines two groups of students at two different levels, belonging to the alternative class and having taken distance education courses. Finally, the author arrives at the results by evaluating distance learning thanks to information technology, which brings a new way of thinking.